Room 706 - Levenson, Ellie (SJP LIT, a Zando Imprint, 2026)
A married woman is trapped with her lover in a hotel under siege: If she knew it would end this way, would it ever have begun? Kate's children and her husband are her whole world. Since marrying young, she's dedicated her life to making her little family grow. But in the last few years, she's carved out something just for herself: hours stolen away with another man. After one midday tryst with her lover, Kate's double life is thrown into chaos when she turns on the TV to find their hotel has been overtaken by an unnamed, dangerous group. As Kate's life hangs in the balance, she is faced with "a gripping exploration of the murky grey areas of marriage, relationships, and womanhood" (Hazel Hayes). Room 706 is a "tense exploration of desire" (Alina Grabowski). Raw, unsettling, and deeply human, it compels you to ask: Would I feel guilt, regret...or relief? "Poignant, immersive, and utterly human, I adored this brilliant novel."-- Sarah Jessica Parker, SJP Lit.